BUDAYA BACA SISWA SMP DI ERA INTERNET - Nurhadi . (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
The Internet is believed to have changed reading habits: deep reading has shifted due to the easy access on the Net. This research is intended to unravel the reading behavior of Junior High School students in the Municipality of Malang. The results indicate that reading is not listed as a favorite past-time: they spend a little time  reading.  The  trend  is  that  they tend  to  spend  their  time  for  accessing  the Internet in a way different from that of the previous time. The analysis shows that there is a positive correlation between reading habit and reading variables related to the Internet.